A GD2-aptamer-mediated, self-assembling nanomedicine for targeted multiple treatments in neuroblastoma theranostics - Liyu Zhang; Meng Wang; Zeen Zhu; Shengquan Chen; Haibin Wu; Ying Yang; Fengyu Che; Qiao Li; Hui Li (Elsevier, 2021)
Because current mainstream anti-glycolipid GD2 therapeutics for neuroblastoma (NB) have limitations, such as severe adverse effects, improved therapeutics are needed. In this study, we developed a GD2 aptamer (DB99) and constructed a GD2-aptamer-mediated multifunctional nanomedicine (ANM) with effective, precise, and biocompatible properties, which functioned both as chemotherapy and as gene therapy for NB. DB99 can bind to GD2+ NB tumor cells but has minimal cross-reactivity to GD2− cells. Furthermore, ANM is formulated by self-assembly of synthetic aptamers DB99 and NB-specific MYCN small interfering RNA (siRNA), followed by self-loading of the chemotherapeutic agent doxorubicin (Dox). ANM is capable of specifically recognizing, binding, and internalizing GD2+, but not GD2−, NB tumor cells in vitro. Intracellular delivery of ANM activates Dox release for chemotherapy and MYCN-siRNA-induced MYCN silencing. ANM specifically targets, and selectively accumulates in, the GD2+ tumor site in vivo and further induces growth inhibition of GD2+ tumors in vivo; in addition, ANM generates fewer or no side effects in healthy tissues, resulting in markedly longer survival with fewer adverse effects. These results suggest that the GD2-aptamer-mediated, targeted drug delivery system may have potential applications for precise treatment of NB.